Dynamic response analysis of concrete filled steel tube tied arch bridge on a slab foundation under moving train load - Zou, Yongnian; Liu, Zhidong; Tian, Changjin; Zhang, Xiaoning; Liu, Bo (Frontiers in Built Environment, 2024)
The analysis of bridge vibration response under train loads is crucial for the operational safety of railway bridge structures. In this study, a three-dimensional coupled dynamic model of train-track-truss arch bridge is established. Based on the numerical simulation results, the effects of different train axle loads and speeds on the vibration response of the truss arch bridge are analyzed, and the time-history changes of the displacement and stress at critical sections of the bridge are revealed. The results show that: during the train operation, the maximum vertical dynamic stress and maximum vertical displacement are linearly related to the train axle load and speed. The greater the train axle load and speed, the larger the maximum vertical dynamic stress and maximum vertical displacement. The maximum vertical acceleration generated during train operation increases linearly with train speed and exponentially with train axle load. The most unfavorable section occurs at the mid-span of the bridge, where the maximum vertical displacement, maximum vertical dynamic stress, and maximum vertical acceleration are all at their peak. This research has significant implications for engineering safety and operation.